“Chrysler Pulled the Trigger”: Competing Understandings of Workplace Violence During the 1970s and Radical Legal Practice - Milloy, Jeremy (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2014)
When “workplace violence” was identified as a pressing social problem in the 1980s and 1990s, experts and policymakers focused on the violence of individuals and the psychological causes of that violence, instead of considering the structural factors associated with the dynamics of class relations and the workplace that produced violence.Yet, workplace violence existed long before the 1980s. This paper investigates three high-profile incidents of workplace violence in the automotive industry of Detroit and Windsor in the 1970s. It explores how these incidents were understood and how such understandings were created and contested, highlighting the pivotal role played by radical legal practice in these contests. It demonstrates that workplace violence often stemmed from factors such as the labour process, racism, and union conflict, and that the success of radical legal practice in raising these issues depended on both the specifics of the crime itself and the political and historical context in which it took place.